2020
DOI: 10.3390/su12187476
|View full text |Cite
|
Sign up to set email alerts
|

E-Procurement Adoption: A Case Study about the Role of Two Italian Advisory Services

Abstract: This paper aims to analyze e-procurement adoption projects with specific focus on the Italian market. E-procurement adoption is critical for organizations, both for its internal efficiency and for the deep impact on sustainability issues. E-procurement adoption, however, is a complex journey as its implementation deals with various obstacles and the adoption costs can limit the overall organizational performance. Advisory services can support organizations in reaching the overall benefits of the e-procurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 60 publications
1
10
1
1
Order By: Relevance
“…This is due to the process being done through an individual profile and to determine if he or she deserves the position. However, these findings are not in line with other researchers where according to a study conducted by Belisari (2020) it was found that e-recruitment is very helpful in the whole issue of selection as screening begins at the first stage of job creation by blocking unqualified people. Mentioned inability to submit their application.…”
Section: E-recruitment Expenses In Selectioncontrasting
confidence: 79%
See 1 more Smart Citation
“…This is due to the process being done through an individual profile and to determine if he or she deserves the position. However, these findings are not in line with other researchers where according to a study conducted by Belisari (2020) it was found that e-recruitment is very helpful in the whole issue of selection as screening begins at the first stage of job creation by blocking unqualified people. Mentioned inability to submit their application.…”
Section: E-recruitment Expenses In Selectioncontrasting
confidence: 79%
“…E-recruitment is the transformation of conventional paper-based recruitment practices into a highly streamlined and digitalized process (Belisari & Appolloni, 2020). The adaptation of e-recruitment is a very complex phenomenon as it tends to address numerous organizational obstacles and overcoming operative costs.…”
Section: Introduction 11 Background Of the Problemmentioning
confidence: 99%
“…There are different types of organizational culture (see Shin and Shin, 2020 ), but none of the frameworks captures all aspects of organizational culture. Organizational culture has been mentioned as the main barrier to change (Belisari et al, 2020 ). The main subthemes for organizational culture derived from the literature that are found to influence technology adoption are presented here: they include vision and goals, strategy , and organizational values and norms .…”
Section: Resultsmentioning
confidence: 99%
“…One of the ways of achieving this competitive advantage is by using technological innovations like digitalization and automation especially when adopted in logistics, transport and purchasing processes [21,22], since logistics activities have a prominent environmental impact on both in-store and online purchasing processes, accounting for more than 75% in these two processes [23]. Another way of achieving competitive advantages is by adopting more sustainable processes that call the attention of customers who are concerned with sustainability.…”
Section: Introductionmentioning
confidence: 99%